Long-Term Tumor-Targeting Effect of E. coli as a Drug Delivery System - Gun Gyun Kim; Hongje Lee; Dan Bi Jeong; Sang Wook Kim; Jae-Seon So (MDPI AG, 2024)
To overcome the limitations of current nano/micro-scale drug delivery systems, an Escherichia coli (E. coli)-based drug delivery system could be a potential alternative, and an effective tumor-targeting delivery system can be developed by attempting to perform chemical binding to the primary amine group of a cell membrane protein. In addition, positron emission tomography (PET) is a representative non-invasive imaging technology and is actively used in the field of drug delivery along with radioisotopes capable of long-term tracking, such as zirconium-89 (89Zr). The membrane proteins were labeled with 89Zr using chelate (DFO), and not only was the long-term biodistribution in tumors and major organs evaluated in the body, but the labeling stability of 89Zr conjugated to the membrane proteins was also evaluated through continuous tracking. E. coli accumulated at high levels in the tumor within 5 min (initial time) after tail intravenous injection, and when observed after 6 days, 89Zr-DFO on the surface of E. coli was found to be stable for a long period of time in the body. In this study, we demonstrated the long-term biodistribution and tumor-targeting effect of an E. coli-based drug delivery system and verified the in vivo stability of radioisotopes labeled on the surface of E. coli.